Linking Organizational Culture to Employee Creativity: Mediating Role of Psychological Well-Being - Ahmed, Athar F M (Archives of Business Research, 2023)
The purpose of this study was to investigate whether organizational culture is related to employee creativity and whether employees’ psychological well-being has a mediating role in this relationship. In order to achieve this aim, data were collected from 310 employees working at the IHH Humanitarian Relief Foundation using the questionnaire technique. Hypotheses were tested with linear regression analysis. The findings showed that market, clan and adhocracy cultures were positively associated with employee creativity. However, it was seen that hierarchy culture had a negative relationship with employee creativity. In addition, it has been understood that psychological well-being mediates the relationship between market culture and employee creativity. It has been revealed that there is a negative relationship between market culture and psychological well-being in the mediation relationship, and a positive relationship between psychological well-being and employee creativity. As far as is known, these relationships have been examined in a single model for the first time. For this reason, it is believed that the findings have valuable insights in terms of practice and theory.